The vigilance-avoidance model of avoidant recognition: An ERP study under threat priming. (30th December 2016) - Zhai, Jing; Chen, Xu; Ma, Jianling; Yang, Qingqing; Liu, Ying
Abstract: Our study examined attachment-related electrophysiological differences in recognition using event-related potentials (ERPs) measured during a study-test paradigm after threat priming. We identified ERP correlates of recognition by comparing the ERPs of attachment-related positive and negative images between avoidant and secure attachment orientations. Our results revealed that the distribution of early old/new effects was broader in avoidant individuals than in secure individuals, and an early parietal old/new effect was observed in avoidant individuals, which reflected their implicit memory. The late old/new effect was found only in secure individuals when evoked by negative pictures, and was not observed in avoidant individuals. The results suggest that avoidant individuals adopt the "vigilance-avoidance" dual-process model to recognize both positive and negative attachment-related stimuli and carry out preferential familiarity matching at the automatic level and avoidant retrieval at the controlled-processing level. Highlights: Threat priming was used to activate attachment system. We examine the avoidant recognition mechanism on different levels of awareness. Avoidant individuals adopted a "vigilance-Avoidance" model during recognition. Positive and negative attachment-related pictures shared same recognize pattern. The use of an undergraduate sample was not conductive to generalize the results.